1985
DOI: 10.3354/dao001169
|View full text |Cite
|
Sign up to set email alerts
|

Development of the PKX myxosporean in rainbow trout Salmo gairdneri

Abstract: Sequenhal development of PKX, the causative agent of prohferahve h d n e y dlsease, is descnbed in rainbow trout Salmo ga~rdnen hchardson by light and electron mlcroscopy Fish were exposed to water contaming the infechous stage of PKX and the parasite was detected 3 wk later Parasites were prominent the following week and they mulhplied by endogeny, binary fission and possibly plasmotomy in the blood and h d n e y intershhum Intershbal nephnbs that is typically assoclated \nth PKD was fust observed 5 wk after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(132 citation statements)
references
References 18 publications
10
122
0
Order By: Relevance
“…Therefore, comparable to our results gained from experimental studies, PKD prevalence and the composition of pathological lesions in infected YOY were not associated with water temperature. It has previously been shown that rainbow trout surviving the clinical phase of PKD are able to completely regenerate renal morphology and that this process is not influenced by water temperature (Ferguson 1981, Kent & Hedrick 1985, Clifton-Hadley et al 1987, Schmidt-Posthaus et al 2012. In accordance with these findings, in our study fish from all tributaries, independent of summer-warm or summercool water, renal morphology could be completely restored during the winter months.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, comparable to our results gained from experimental studies, PKD prevalence and the composition of pathological lesions in infected YOY were not associated with water temperature. It has previously been shown that rainbow trout surviving the clinical phase of PKD are able to completely regenerate renal morphology and that this process is not influenced by water temperature (Ferguson 1981, Kent & Hedrick 1985, Clifton-Hadley et al 1987, Schmidt-Posthaus et al 2012. In accordance with these findings, in our study fish from all tributaries, independent of summer-warm or summercool water, renal morphology could be completely restored during the winter months.…”
Section: Discussionsupporting
confidence: 81%
“…T. bryosalmonae infects fish through the skin and gills , Longshaw et al 2002. After invasion, this parasite is distributed systemically, with the kidney as the main target organ (Kent & Hedrick 1985). Here, T. bryo salmonae multiplies and differentiates from extra sporogonic stages, mainly in the renal interstitium, to sporogonic stages in the tubular lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hoferellus cyprini (LOM andDYKOVA, 1985, MOLNAR and), Sphaerospora sp. (FISCHER-SCHERL et al, 1986), "PKX" (KENT and HEDRICK, 1986) and Myxobilatus legeri (MOLNAR, 1988) have also been reported as having intracellular stages. Moreover, DANIELS et al (1976) showed intra cellular parasites in the epithelium of rainbow trout exposed to water containing some stage of Myxobolus cerebralis.…”
Section: Methodsmentioning
confidence: 99%
“…The severe inflammation of the kidney that characterizes the disease is caused by PKX, the vegetative stage of a poorly understood myxozoan (Kent & Hedrick 1986). Although the precise taxonomic position of PKX has not been determined, recent observations by Hedrick e t al.…”
Section: Introductionmentioning
confidence: 99%